The Reproducibility of YAG:Ce Ceramics Formed by Electron Beam Assisted Synthesis; Energy Fluxes and Radiation Effects (EFRE-2020 online) - Karipbaeyev Zh. Zhakyp; Lisitsyn V. M. Viktor Mikhailovich; Alpyssova G. Gulnur; Grechkina T. V. Tatiana Valerievna; Kukenova A. Aizat; Mussakhanov D. Dossymkhan; Shenarsheev V. Vladimir (2020, 2020)
Title screen